2018
DOI: 10.1108/ilt-04-2017-0095
|View full text |Cite
|
Sign up to set email alerts
|

Optimizations of RZ5-TiC magnesium matrix composite wear parameters using Taguchi approach

Abstract: Purpose The advancement in modern manufacturing technology generated the need to develop new materials for better wear resistance. The purpose of this paper is to use the Taguchi optimization approach to examine which wear parameter significantly affects weight loss and coefficient of friction for RZ5-TiC composite. It is a simple and efficient method to find performance of wear parameter using minimum experimental runs. Design/methodology/approach RZ5-TiC composites were prepared using RZ5 as matrix, reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Thus, result in improvement of wear resistance because of the improvement of the hardness. The hardness of the composite is improved from 75 to 105 VHN (Mehra et al , 2018a, 2018b, 2018c, 2018d, 2018e). The influence of the Wt.% of TiC and sliding distance for weight loss are relatively high as compared to applied load as shown in Table II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, result in improvement of wear resistance because of the improvement of the hardness. The hardness of the composite is improved from 75 to 105 VHN (Mehra et al , 2018a, 2018b, 2018c, 2018d, 2018e). The influence of the Wt.% of TiC and sliding distance for weight loss are relatively high as compared to applied load as shown in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the melt is casted. Figure 1 shows the scanning electron microscope (SEM) microstructure of pin profile before wear test of RZ5 Mg matrix alloy and its composites (Mehra et al , 2018a, 2018b, 2018c, 2018d, 2018e).…”
Section: Methodsmentioning
confidence: 99%
“…Taguchi method is an approach based on the orthogonal array and is having the capacity of giving less variance for the parameters which control the experiments when it is set at optimum condition [49]. B A M Pasha et al has stated that it is a method where the expenses are meager and are being used nowadays by the researchers to formulate a relationship between the impact of parameters and it is interactions in experiments [48].…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…In this work done by Satnam Singh et al the selected the normal load, track diameter and sliding distance as the parameters which are varied at 3 levels [50]. It is written by D Mehra et al that they have used an L27 orthogonal array, which means there are 27 experiments that are represented in the 27 rows followed by three levels at 13 columns [49]. M A Almomani has noted that the effect of test parameters and percentage weights of the reinforcing materials against the wear rate is being analyzed by using Taguchi's L16 orthogonal array at the levels of normal load and sliding speed [51].…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…The literature below shows some of the research activities in the property enhancement of magnesium and its alloys. The mechanical behaviour of magnesium composite with titanium carbide was investigated, and a considerable improvement in hardness and tensile strength was observed (Mehra et al , 2018). The mechanical behaviour of magnesium composite with TiO 2 was investigated (Hassan et al , 2017), and the improved ductility was observed.…”
Section: Introductionmentioning
confidence: 99%